(untitled) (Global Journal of Science Frontier Research, 2018)
In this paper, first order chemical reactant will be analyzed to study the effect of the fluctuation of MHD turbulence before the ultimate phase of decay in present of dust particles in a rotating system at four point correlation. Following Deissler’s approach two, three and four point correlation equations have been obtained, and the set of correlation equations is made determinate by neglecting the quintuple correlations in comparison to the third and fourth order correlation terms. By taking Fourier-transforms, the correlation equations are converted to spectral form. Finally, integrating the energy spectrum over all wave numbers. The energy decay of MHD turbulence for first-order reactant in the presence of dust particles in a rotating system is obtained, and the result is shown graphically in the text.